Designing work for 21st Century bodies and lifestyles - Straker, Leon (2012)
Ergonomics developed in the middle of the 20th century with a physical focus on avoiding fatigue and overexertion, which suited the status of bodies and lifestyles at the time. Contemporary bodies in affluent communities are fat and unfit with inactive lifestyles. Contemporary work often demands sustained sedentary behaviour and is thus an important contributor to not only musculoskeletal disorders but also the substantial burdens associated with inactivity related disorders such as obesity, diabetes and cardiovascular disease. Public health responses to the growing burden from inactivity related disorders have to date focussed on leisure time exercise and transport to and from work. Ergonomics has an excellent opportunity to make a substantial contribution to population health by using its expertise in workplace interventions and postural variation. However physical ergonomics needs to change its paradigm to design work to increase, rather than decrease, physical loads at work through the minimisation of sustained sedentary behaviour and encouragement of activity. © Straker: Licensee HFESA Inc.